Low-latitude equinoctial spread-F occurrence at different longitude sectors under low solar activity - Pezzopane, M. (2013)
We present the results of a comparative study of spread-F signatures over five low-latitude sites: Chiangmai (CGM; 18.8° N, 98.9° E, mag. Lat. 8.8° N), Thailand; Tanjungsari (TNJ; 6.9° S, 107.6° E, mag. Lat. 16.9° S), Indonesia; Palmas (PAL; 10.2° S, 311.8° E, mag. Lat. 0.9° S) and São José Dos Campos (SJC; 23.2° S, 314.1° E, mag. Lat. 14.0° S), Brazil; and Tucumán (TUC; 26.9° S, 294.6° E, mag. Lat. 16.8° S), Argentina. The investigation was based on simultaneous ionograms recorded by an FMCW (frequency-modulated continuous-wave) at CGM, an IPS-71 (digital ionosonde from KEL aerospace) at TNJ, a CADI (Canadian Advanced Digital Ionosonde) at PAL and SJC, and an AIS-INGV (Advanced Ionospheric Sounder – Istituto Nazionale di Geofisica e Vulcanologia) at TUC, during the equinoctial periods March–April (R12 = 2.0 and R12 = 2.2) and September–October (R12 = 6.1 and R12 = 7.0) 2009, for very low solar activity. Spread-F signatures were categorized into two types: the range spread-F (RSF) and the frequency spread-F (FSF). The study confirms that the dynamics and the physical processes responsible for these phenomena are actually complicated. In fact, the features that arise from the investigation are different, depending on both the longitude sector and on the hemisphere. For instance, TUC, under the southern crest of the ionospheric equatorial ionization anomaly (EIA), shows a predominance of RSF signatures, while both SJC, under the southern crest of EIA but in a different longitude sector, and CGM, under the northern crest of EIA, show a predominance of FSF signatures. Moreover, the spread-F occurrence over the longitude sector that includes CGM and TNJ is significantly lower than the spread-F occurrence over the longitude sector of PAL, SJC, and TUC.